Pengaruh Financial Literacy, Financial Self-Efficacy, dan Financial Attitude terhadap Pengelolaan Keuangan Mahasiswa Akuntansi UNTAG Surabaya - Imeltiana Imeltiana; Hwihanus Hwihanus (Universitas 45 Surabaya, 2024)
The purpose of this study is to determine how accounting students Untag Surabaya manage their finances in relation to financial literacy, financial self-efficacy, and financial attitude. This study employed a quantitative approach using SPSS support tool version 25. This study's participant population is an accounting student of Untag Surabaya force 2021. A total of 100 students were selected as samples of this research since they fulfilled the requirements. Double linear regression analysis methods are employed in the study of hypotheses in this study. The hypothesis test's outcome indicates that the financial literacy variable has at count value (1,893) bigger than the t table (1,661) at the an alpha significance level of 0.05, meaning that the economic literacy has an influence on student financial management. The financial self-efficacy has a T count value (1,588) lower than the table t value (1,661), at the significance rate of 0.05, thus it can be inferred that the Financial self-eficacy does not affect student finance management. In addition, financial literacy, that financial self-efficacy, and financial attitudes impact the money management of students.